Tingkat Pengetahuan dan Prilaku Masyarakat Tentang Upaya Peningkatan Imunitas Tubuh dalam Pencegahan Infeksi COVID-19 - Ramadhania, Alifira; Farhan, Fanny Septiani (Rumah Sakit Ibnu Sina, Makassar, 2021)
World health organization has declared the COVID-19 virus outbreak which is the cause of respiratory disease as a pandemic since March 2020. In Indonesia, COVID-19 infection reached more than 200,000 positive cases. With the increasing number of positive cases of COVID-19, it is necessary to apply prevention to protect oneself from this virus infection, one of which is by increasing the body's immunity such as doing physical activities, consuming vitamins and herbs. This study aims to find out the level of knowledge and behavior of RT 05/03, Rempoa Residence in an effort to improve the body's immune system to avoid COVID-19 infection. The method used was observational descriptive research using a total sampling technique with 162 samples with an adult (19-59 years old) and elderly (more than 60 years old). Sampling using a questionnaire shared with Google Form. The level of knowledge about COVID-19 in RT 05/03, Rempoa Residence, 88,9% has good knowledge, 11,1% enough knowledge, and no one has insufficient knowledge, as well as doing prevention to avoid COVID-19 infection. The results found that the RT 05/03, Rempoa Residence, has a good and enough level of knowledge about COVID-19, and conducts behavior to increase body immunity for the prevention of COVID-19 infection.